Twórczość komiksowa uchodźców ukraińskich w edukacji na rzecz transkulturowości w klasach I–III – pilotażowa koncepcja pracy - Lisowska, Kinga (Kultura-Społeczeństwo-Edukacja, 2023)
The article presents a pilot concept of using comic books work of Ukrainian youth – war refugees in the field of work for transculturalism in grades I–III. It is an attempt to take a different look at educational activities in the perspective of dynamically changing cultural structures of European and world societies. The presented assumptions thus answer the question: how can the comic books of Ukrainian youth be used to create a pilot concept of work in the field of education for transculturalism in grades I–III and to develop the right concept of work in further scientific activities (supported by an appropriate research procedure)? Two methods of data collection were adopted in the research: a case study of young female refugee comic book authors using a problem-focused interview; analysis of the content of the comic book, which was used in the creation of a pilot concept of work for transculturalism. The article also focuses on the theoretical assumptions of the phenomenon of transculturalism itself. The comic books of Ukrainian youth can be an excellent source of work in the field of transculturalism, which should be implemented in the school space based on regional and intercultural education already functioning in the education system. The way to move away from the native – closed cultural structure and open it on the periphery to what is new/different/valuable. The pilot concept of work should be implemented in the educational environment of grades I–III and its assumptions should be checked on this ground. This will allow you to develop and implement the right concept of work.